Experimental Study on Equivalent Strength of Induced Joints with consideration to Influence of Concrete Strength, Inducer Spacing, and Concrete Age - Xiaofei Zhang; Peipei Wei; Xin Zhang; Tao Yan; Gangfeng Zheng; Wenwei Zhang (Advances in Civil Engineering)
To prevent the occurrence of temperature cracking, the induced joints of dams are typically arranged to reduce the tensile strength and orderly guide the crack to form at an induced joint, which can protect the dam structure. The state of the joint surface and the equivalent strength and arrangement of the induced joints have important practical significance for preventing the disorderly cracking of the dam. In this study, the concrete strength, inducer spacing, and concrete age were considered as variable conditions to perform axial tension tests on roller compacted concrete (RCC) bidirectional induced joints. A finite element software was used for numerical simulation, and the simulation results were compared with the experimental results. The equivalent strength of the RCC induced joints increased with the spacing of the induced joints, but the rate of increase gradually declined. The equivalent strength of the RCC induced joints rapidly increased in the early stage, but the strength weakening degree was different at different concrete ages. The strength weakening degree of the induced joint section decreased as the concrete strength increased. These results provide a reference for the setting of induced joints in practical engineering.